MAKNA KOSAKATA “JATUH” DALAM BAHASA SUNDA DAN BAHASA JAWA - Emma Maemunah (Aksara, 2017)
Sundanese and Javanese language derived from the same proto language. There are many similarities in both languages. The similarities are in the form and meaning. This study discusses the form and the meaning of vocabularyof "fall" in Sundanese and Javanese. The aim of this study is to describe the form of "fall" in Sundanese and Javanese as well as the shift of meaning happened to the vocabulary. Using the comparative historical linguistics and semantics, the vocabularyof "fall" will be analyzed qualitatively. The data are list of vocabulary of "fall" in Sundanese and Javanese. Data are qualified in accordance with the objectives to be achieved. The analysis showed that the vocabulary of "fall" of Sundanese and Javanese have similarities, in both form and meaning. In addition, There are also some vocabularies which shifted (expanded and narrowed) and changed the meaning.